The Effect of Formalin Fixation on Resection Margins in Colorectal Cancer. (October 2019) - Lam, David; Kaneko, Yui; Scarlett, Adam; D'Souza, Basil; Norris, Richard; Woods, Rodney
Resection margins in colorectal cancer carry clinical significance with regard to disease recurrence risk and selection for multimodal adjuvant therapy, especially with circumferential resection margins in rectal cancer. Colorectal cancer specimens are routinely fixed in formalin, which results in specimen and tumor-free margin shrinkage. However, the effects of shrinkage have not traditionally been taken into account when analyzing tumor-free margins. In this prospective study, 46 colorectal cancer specimens were measured in the fresh state and subsequently after formalin fixation for total specimen length, distal resection margin, and radial margin (circumferential resection margin for rectal cancer). The mean reduction after formalin fixation was 17.48 mm (14.7%) for distal resection margin and 1.20 mm (10.5%) for radial margin. For rectal cancer, circumferential resection margin reduction was 0.88 mm (11.8%); this was not affected by neoadjuvant chemoradiotherapy. Duration of formalin fixation did not significantly affect the extent of margin shrinkage. This is the first study to evaluate the effect of formalin fixation on radial resection margins, specifically as it relates to rectal cancer, and it demonstrates that shrinkage from formalin fixation should be a consideration in decision-making where the magnitude of tumor-free margins is small.